Simulator GNS3 dan Wireshark Sebagai Model Virtual Pembelajaran Pratikum Jaringan Komputer - Raisul Azhar; I Putu Hariyadi (Universitas Pendidikan Mandalika (UNDIKMA), 2017)
Impkementation of practicum on the course of computer networking at vocational school (SMKN1 Sambelia) and (SMKS Al Ma’rif Qomarul Huda) was through a convensional methods with incomplete equipments. In practicum activity should be supported by a various eqipments with different functions, such as; router, hub, accent firewall, but relatively expensive for procurement. Therefore, the school unable to fullfill the practicum equipments and potentially disturb the instructional process. To solve this condition, a virtual instructional methods could be implemented through GNS3 simulator completed with the network analyzer tools. The research method was Network Development Life Cicle and simulator utility of measurement functionality in the instructional of computer networking.